Karakteristik Mutu Jamur Tiram (Pleurotus ostreatus) Menggunakan Berbagai Metode Pengemasan pada Penyimpanan Suhu Rendah - Ayu Aulia Aftukha; Dian Purbasari (The University of Lampung, 2021)
Oyster mushrooms (Pleurotus ostreatus) include holticulture products that have a high moisture content. High water content can speed up the process of respiration rate, causing oyster mushrooms to easily damage. An alternative that can be used to overcome the problem of oyster mushroom damage is to slow down the rate of respiration by packaging. The purpose of this study is to analyze the quality characteristics of oyster mushrooms as well as the influence of packaging methods and storage time at low temperatures (5 °C). This study used two factors, namely packaging method and storage length. The data was analyzed using factorial anova two mix factors with tests (a = 5 %), if obtained differently real then conducted follow-up test Tukey. The results showed the best packaging method is found in vacuum packaging with the highest texture value of 0,004 N/mm2. The highest color brightness value is 83,15. The lowest moisture content value is 88%. The lowest water activity value was 0,895 and the lowest weight was 2,47%. Keywords: oyster mushrooms, packaging, storage, temperature, quality